Differences in ocular high order aberrations before and after small incision lenticule extraction for correction of myopia: a systematic review and meta-analysis - Du, Yifan; Di, Yu; Yang, Shan; Mo, Fei; Cui, Ge; Chen, Di; Li, Ying (Frontiers in Medicine, 2024)
Objective To examine the causes and factors that lead to high order aberration (HOA) during the treatment of myopia using small incision lenticule extraction (SMILE), as well as the differences between SMILE and other corneal refractive surgeries through a systematic review and meta-analysis. Methods A systematic search was conducted from January 2015 to February 2023 in Pubmed, Embase, Web of Science, and Google Scholar databases to gather relevant studies on SMILE and HOA. Studies meeting specific criteria were chosen, and clinical data was retrieved for analysis. Results This meta-analysis resulted in the inclusion of 19 studies involving 1,503 eyes. Pooled results showed significant induction of total HOA (tHOA, d = −0.21, p < 0.001), spherical aberration (SA, d = −0.11, p < 0.001) and coma aberration (CA, d = −0.18, p < 0.001) after SMILE compared to pre-SMILE, while no significant change in trefoil aberration (TA) was observed (d = −0.00, p = 0.91). There was a significantly lower induction of tHOA after SMILE compared to femtosecond laser-assisted in situ keratomileusis (FS-LASIK, d = 0.04, p < 0.001), and no significant difference was observed compared to wavefront aberration-guided (WFG) refractive surgery (d = 0.00, p = 0.75). There was also a significant association between different levels of myopia and astigmatism, duration of follow-up, lenticule thickness, and preoperative central corneal thickness (CCT) on the induction of tHOA after SMILE (p < 0.05), while the higher preoperative myopia group (sphere > -5D), lower preoperative astigmatism group (cylinder ≤ -1D), larger lenticule thickness group (lenticule thickness > 100 μm), shorter follow-up group (follow-up 1 month postoperatively) and the thicker CCT group (CCT > 550 μm) brought a significant induction of tHOA compared to the opposite comparison group (p < 0.001). Conclusion While SMILE can induce HOA significantly, it induces less HOA than FS-LASIK. Postoperative HOA following SMILE can be affected by factors such as myopia, astigmatism, lenticule thickness, CCT, and duration of follow-up. Future research should continue to explore techniques to decrease the induction of HOA by using this methodology. Systematic review registration https://www.crd.york.ac.uk/prospero/.